2007
DOI: 10.1002/pd.1710
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between prenatal ultrasound and fetal autopsy findings in fetal anomalies terminated in the second trimester

Abstract: Evaluation of fetal autopsies following TOP enables diagnosis of pathologies undetected by prenatal ultrasound alone, leading to better preconceptional counseling for subsequent pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 20 publications
3
55
2
2
Order By: Relevance
“…There is complete agreement of autopsy and US findings in 46% to 78.4% of cases. [3][4][5][6] Our study showed complete concordance in 72.5% of the cases. In 30 of 91 cases (33%), the autopsy changed the diagnosis or was essential to establish it.…”
Section: Discussionmentioning
confidence: 57%
“…There is complete agreement of autopsy and US findings in 46% to 78.4% of cases. [3][4][5][6] Our study showed complete concordance in 72.5% of the cases. In 30 of 91 cases (33%), the autopsy changed the diagnosis or was essential to establish it.…”
Section: Discussionmentioning
confidence: 57%
“…This important issue is discussed widely elsewhere [15][16][17][18][19][20] . Many Israeli couples are reluctant to consent to post-abortion autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, in up to one-quarter of cases, additional information which changes the underlying diagnosis or the information given to parents during counselling may be acquired from a formal autopsy. [5][6][7][8][9] This figure may be higher in paediatric rather than perinatal cases. 1 Several studies have also shown a significant discrepancy rate between what clinicians think is the cause of death and full traditional autopsy findings, 3,10 and error rates can be as high as 50% on medical certificates in stillbirths.…”
mentioning
confidence: 99%